Pendampingan Pemasaran Berbasis Digital bagi Pelaku Usaha Bibit Buah dan Tanaman Hias di Kabupaten Kampar - Muhammad Amin (Universitas Pahlawan Tuanku Tambusai, 2026)
Fruit seedling and ornamental plant enterprises in Kampar Regency have significant economic potential; however, their marketing practices are still predominantly conventional, resulting in limited market reach. This community service program aimed to enhance the digital marketing capacity of business actors through an Asset-Based Community Development (ABCD) approach in Sungai Pinang, Kualu Nenas, and Rimbo Panjang villages. The program was implemented through the stages of discovery, dream, design, and destiny, employing observation, interviews, focus group discussions, questionnaires, and hands-on mentoring. The results showed an improvement in participants’ digital literacy and skills, indicated by an average increase of 34% in pretest–posttest scores. Business actors were able to produce simple promotional content, manage social media and marketplace accounts, and develop basic branding. In addition, village-based digital communities were established as platforms for continuous learning. The findings imply that the ABCD approach is effective as a sustainable, locally grounded digital marketing mentoring model for rural horticultural MSMEs.